How Big is Illicit Cigarette Trade in the Philippines? - Austria, Myrna S. (Animo Repository, 2021)
Illicit cigarette trade or the manufacture, distribution, and sale of cigarettes that evade taxes and violate trademarks, persists in the Philippines. Enhancing the affordability and availability of cigarettes undermines the effectiveness of the series of tax policy reforms meant to lower, if not eliminate, tobacco use in the country. Worse, it results in a loss in government tax revenues. This Policy Brief presents the estimates and recommends policy actions to address the problem. The results from residual methods provide a strong presence of illicit cigarette trade in the country. The magnitude ranges from 3.3% to 42.8% of total cigarette consumption, resulting in a loss in tax revenue from Ph11.96 billion to PhP40 billion.